KONFIRMATORI PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUTUSAN MAHASISWA MEMILIH STUDI DI AKADEMI KEBIDANAN JEMBER - Santoso, Nugroho Edie; Dimyati, Mohamad; Suryaningsih, Ika Barokah (BISMA: Jurnal Bisnis dan Manajemen, 2016)
Abstract: The purpose of this study was to determine the influence of marketing mix on the students’ decision to study inthe Midwifery Academy, Jember. The objects of the study were students of the Midwifery Academy, Jember. This study used full sampling method with a sample size of 189 respondents. Multiple linear regression with confirmatoryapproach was used to test the hypothesis. The results showed that the variables of product, price, place, people, physical evidence, and process have significant effect on students’ decision to study in the Midwifery Academy, Jember. Keywords: Product, Price, Place, People, Physical Eevidence, Pocess, and Decision